Role of fractional flow reserve in guiding intervention for borderline coronary lesions. Issue 3 (1st September 2014) - Shi, Xuekun; Cheng, Lu
Abstract : Objective: This study investigated the clinical efficacy and value of fractional flow reserve (FFR) in guiding the treatment of borderline coronary lesions. Methods: Forty-three patients with borderline coronary lesions, as demonstrated by coronary angiography, and who had FFR measurements were selected. The patients were grouped according to FFR values. All patients were evaluated 6 months after surgery to record major adverse cardiac events (MACE [sudden cardiac death, non-fatal myocardial infarction, or revascularization]) and recurrence of angina pectoris. Results: After the 6-month follow-up, no sudden cardiac deaths or myocardial infarctions occurred in either group, and there were no statistically significant differences ( P >0.05). Inter-group comparisons showed that in the groups with a FFR<0.75, the recurrence rate of angina pectoris in the PCI group was significantly lower than the drug therapy group (0.08% vs. 0.27%, P <0.05). In contrast, the recurrence rate of angina pectoris in the PCI group among the groups with a FFR<0.75 revealed no statistical significance when compared to the groups with a FFR≥0.75 (0.08% vs. 0.05%, P >0.05). The recurrence rate of angina pectoris in the simple drug therapy group among the groups with a FFR<0.75 was higher than the same groups with a FFR≥0.75 (0.27% vs. 0.05%, P <0.05). Conclusion: When coronary intervention is used to treat borderline lesions, guiding interventional therapy with measurement of FFR does not increase the incidence of adverse cardiovascular events in the short term and can better guide PCI therapy.